The estimation of live weight of Nigerian cattle from linear body measurements - Ross, J.G. (1958)
Compares the efficiency of the modified Johnson Formula and the Hearth Girth Scale methods of weight estimation in cattle using the Sokoto Gudali Zebu, the N'Dama and the Muturu breeds of Nigeria. Compares results with previous work on zebu and European cattle.